2022
DOI: 10.3390/membranes12050444
|View full text |Cite
|
Sign up to set email alerts
|

Barrier Membrane in Regenerative Therapy: A Narrative Review

Abstract: Guided bone and tissue regeneration remains an integral treatment modality to regenerate bone surrounding teeth and dental implants. Barrier membranes have been developed and produced commercially to allow space for bone regeneration and prevent the migration of unwanted cells. Ideal membrane properties, including biocompatibility, sufficient structural integrity and suitable shelf life with easy clinical application, are important to ensure good clinical regenerative outcomes. Membranes have various types, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 84 publications
(103 reference statements)
0
17
0
Order By: Relevance
“…In recent years, guided bone regeneration (GBR) treatment has been regarded as a successful and reliable technique for repairing alveolar bone defects 3 . Studies have shown that barrier membranes are crucial for proper bone regeneration during the GBR process, as they need to occlude the faster growing soft tissue to invade into the bone defect underneath, thus providing the appropriate space, time for the comparatively less slowly growing bone tissue to regenerate 4 . To achieve optimal bone regeneration, GBR membranes should possess good biocompatibility, proper mechanical characteristics for space maintenance, ideal resorption time to prevent epithelial cell migration into the bone defect and provide enough time for bone regeneration, and the ability to stimulate bone formation 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, guided bone regeneration (GBR) treatment has been regarded as a successful and reliable technique for repairing alveolar bone defects 3 . Studies have shown that barrier membranes are crucial for proper bone regeneration during the GBR process, as they need to occlude the faster growing soft tissue to invade into the bone defect underneath, thus providing the appropriate space, time for the comparatively less slowly growing bone tissue to regenerate 4 . To achieve optimal bone regeneration, GBR membranes should possess good biocompatibility, proper mechanical characteristics for space maintenance, ideal resorption time to prevent epithelial cell migration into the bone defect and provide enough time for bone regeneration, and the ability to stimulate bone formation 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were also reported by 5 more reviewed studies which either used NCHA paste or NCHA along with plasticizer like silica gel ( Strietzel et al, 2007 , Kasaj et al, 2008 , Heinz et al, 2010 , Pietruska et al, 2012 , Al Machot et al, 2014 ). Although the use of a barrier membrane has been considered imperative in GBR of intrabony defects ( Alauddin et al 2022 ), only 3 out of the 14 reviewed studies used a collagen barrier membrane along with NCHA ( Gholami et al, 2012 , Singh et al, 2012a , Singh et al, 2012b , Elbattawy and Ahmed, 2021 ). All of these studies reported significantly improved bone formation after 6 months of grafting.…”
Section: Discussionmentioning
confidence: 99%
“… 75 From a wide range of synthetic polymers, Poly lactic acid (PLA), PCL, PLCL, PGA, PLGA and Poly vinyl alcohol (PVA) are the most used in periodontal research. 76 PLA, which is used as a bioabsorbable membrane in some research, demonstrates high hydrophilicity, low cytotoxicity, high alkalinity and due to its predictable results, it is widely used in different periodontal studies. 39 , 77 , 78 In addition, PCL is another popular synthetic polymer with biocompatibility and biodegradability features.…”
Section: Synthetic Polymer-based Layered Scaffolds For Periodontal Re...mentioning
confidence: 99%